The Effect of Lansium domesticum Corr. (Duku) Seed Extract on Wound Healing (Journal of Nobel Medical College, 2020)
Background: A wound is an injury caused by a cut, blow, or any else that typically involves laceration. For the treatment of infections and promoting wound healing, povidone-iodine is usually used but sometimes it can lead to irritation. The researcher would like to develop Lansium domesticum Corr. (duku) seed extract ointment to promote wound healing.Materials and Methods: This experimental study was done on 30 rats which are divided into six groups namely negative control, positive control (povidone-iodine 10%), the experimental group with three different concentration of Lansium domesticum seed extract ointment (2.5%, 5%, and 10%) and followed for three days to assess wound size. Approval was acquired by the Research Ethics Committee of the Sriwijaya University Faculty of Medicine, Palembang, Indonesia. In vitro capacity of Lansium domesticum extract also assessed by measuring inhibitory diameter.Results: After three days of treatment, there is a significant difference in wound closure for all groups (p